Optimal inductor design for a 6.6 kW buck-boost converter - Xu, Dongchen (Nanyang Technological University, 2024)
Magnetic components (such as transformers and inductors) play crucial roles in switch-mode power supplies, serving tasks like electrical isolation, voltage transformation, and energy buffering. They significantly impact the efficiency, size, and power density of the transformer. As the switching frequency of the transformer continues to increase, the accuracy of high-frequency magnetic component design becomes more prominent in determining transformer performance. Therefore, optimizing the design and rational application of magnetic components is of utmost importance in enhancing the performance of power electronic converters. Achieving precise measurement and calculation of magnetic core losses is a prerequisite and essential condition for all these endeavors.